Does Asymptomatic, Mild and Moderate Covid-19 Infection in the First and Second Trimester Affect Pregnancy Outcomes? - Sever, Baris (2023)
Objectives: To evaluate the effects of asymptomatic, mild and moderate Covid-19infection in the 1st and 2nd trimesters on pregnancy outcomes. Material andmethods: The study was performed among patients who applied to the PerinatologyDepartment of Izmir University of Health Sciences, between October 2021 andJuly 2022. Pregnant women who had asymptomatic, mild and moderate Covid-19infection in the 1st and 2nd trimesters were registered and their pregnancyprocesses were followed. Results: A total of 437 patients participated in the study.The numbers of asymptomatic, mild and moderate Covid-19 patients were 142, 157and 138, respectively. Each group was analyzed as 1st and 2nd trimester subgroupsaccording to the time of Covid-19 infection. The mean age of patients with moderateCovid-19 was higher than with mild/asymptomatic Covid-19 (p=0.021). Body massindex was found to be higher in patients with moderate Covid-19 compared topatients with mild/asymptomatic infection (p=0.048). Preterm labor (between 34thand 37th weeks) was significantly higher with moderate Covid-19 infection (p=0.041).This significant increase was mainly due to the preterm birth rate in patients withprevious Covid-19 infection in the 2nd trimester. There was no significant changein the rates of cesarean section, hypertensive disorders of pregnancy, fetal loss,intrauterine growth restriction, cholestasis of pregnancy and gestational diabetes.Conclusions: The effects of Covid-19 infection in early pregnancy (1st and 2ndtrimester) are still the subject of research. Moderate Covid-19 infection, especially inthe 2nd trimester, may lead to an increase in the rate of preterm birth.